Angiotensin II: a major regulator of subcutaneous adipose tissue blood flow in humans. - Goossens, G; McQuaid, SE; Dennis, A; Baak, v; Blaak, E; Frayn, K; Saris, W; Karpe, F (2006)
We investigated the functional roles of circulating and locally produced angiotensin II (Ang II) in fasting and postprandial adipose tissue blood flow (ATBF) regulation and examined the interaction between Ang II and nitric oxide (NO) in ATBF regulation. Local effects of the pharmacological agents (or contralateral saline) on ATBF, measured with 133Xe wash-out, were assessed using the recently developed microinfusion technique. Fasting and postprandial (75 g glucose challenge) ATBF regulation was investigated in nine lean healthy subjects (age, 29 +/- 3 years; BMI, 23.4 +/- 0.7 kg m(-2)) using local Ang II stimulation, Ang II type 1 (AT1) receptor blockade, and angiotensin-converting enzyme (ACE) inhibition. Furthermore, NO synthase (NOS) blockade alone and in combination with AT1 receptor blockade was used to examine the interaction between Ang II and NO. Ang II induced a dose-dependent decrease in ATBF (10(-9)m: -16%, P = 0.04; 10(-7)m: -33%, P < 0.01; 10(-5)m: -53%P < 0.01). Fasting ATBF was not affected by ACE inhibition, but was increased by approximately 55% (P < 0.01) by AT(1) receptor blockade. NOS blockade induced a approximately 30% (P = 0.001) decrease in fasting ATBF. Combined AT1 receptor and NOS blockade increased ATBF by approximately 40% (P = 0.003). ACE inhibition and AT1 receptor blockade did not affect the postprandial increase in ATBF. We therefore conclude that circulating Ang II is a major regulator of fasting ATBF, and a major proportion of the Ang II-induced decrease in ATBF is NO independent. Locally produced Ang II does not appear to regulate ATBF. Ang II appears to have no major effect on the postprandial enhancement of ATBF.